Nanoparticle friction and contact ageing - Feldmann, Michael; Justus Liebig University Giessen (My University, 2013)
The phenomenon of friction permeates the vast majority of mechanical systems, but despite its ubiquity, the basic mechanisms leading to friction are currently not very well understood. Instead, the characterization of friction is mostly limited to phenomenological descriptions.A promising way to improve on the comprehension of friction on a fundamental level is guided by the fact that macroscopic contacts in general can be broken down into many smaller sub-contacts. It thus is imperative to investigate friction of these smallest units, the so-called single asperity nanoscale contacts, to gain insight into the basic principles governing friction. An essential issuein this context is the emergence of contact ageing, which i.a. is the cause for static friction. Contact ageing is observed in macroscopic friction experiments on a regular basis, but its existence in nanoscale contacts could only recently be demonstrated for the first time.Nanoparticles manipulated under vacuum conditions using friction force microscopes represent an excellent experimental model system in this endeavor to study frictional properties of single asperity contacts. In this work, experimental methods to manipulate nanoparticles and to study their frictional characteristics were developed and implemented. This framework allowed to conduct fundamental experiments regarding the friction kinetics of antimony nanoparticles on graphite substrates with respect to their velocity- and temperature-dependence.By carrying out Monte Carlo simulations of a newly devised nanoscale friction model, two competing processes were identified as having a major impact on the friction kinetics, namely thermal activation as well as ageing of the contacts. The observation of stick-slip-type friction in consecutive experiments allowed to directly quantify contact ageing in nanoparticle friction, exposing an ageing law with logarithmic dependence on stationary hold times.Complementary measurements revealed two qualitatively different contact ageing phenomena for point-like contacts at varied temperatures. In silica-gold contacts, ageing during lateral movement due to gold neck shearing could be registered, while silica-silica contacts exhibited ageing of stationary contacts, comparable to the contact ageing found for antimony nanoparticles.All findings highlight the fundamental significance of contact ageing in nanoscale friction, especially for the case of nanoparticle kinetics.

Reibungsphänomene sind für eine Vielzahl von mechanischen Systemen von zentraler Bedeutung. Die zur Reibung führenden Mechanismen sind jedoch bisher nicht zufriedenstellend verstanden. Stattdessen beschränkt sich die Charakterisierung von Reibung vielfach auf phänomenologische Beschreibungen. Ein vielversprechender Weg, um das grundlegende Verständnis von Reibung zu verbessern, lässt sich von der Erkenntnis ableiten, dass makroskopische Kontakte im Allgemeinen aus vielen mikroskopischen Subkontakten aufgebaut sind. Es ist daher unumgänglich die Reibung dieser Subkontakte, den sogenannten Einzelasperitätkontakten, zu untersuchen, um Erkenntnisse bezüglich der elementaren Reibungsprozesse zu gewinnen. Ein Phänomen von zentraler Bedeutung ist in diesem Zusammenhang das Auftreten von Kontaktalterung, welches unter anderem die Ursache für die Entstehung von Haftreibung darstellt. Diese Kontaktalterung wird in makroskopischen Reibungsexperimenten regelmäßig beobachtet. Das Auftreten von Kontaktalterung in Nanokontakten konnte jedoch erst kürzlich zum ersten Mal beobachtet werden.Die Manipulation von Nanopartikeln unter Vakuumbedingungen mittels Reibungskraftmikroskopie stellt ein exzellentes Modellsystem zur Untersuchung von Reibung und Kontaktalterung in ausgedehnten Ein-Asperität-Kontakten dar. Für die vorliegende Arbeit wurden verschiedene Methoden zur definierten Manipulation und Reibungsbestimmung von Nanopartikeln entwickelt und implementiert. Dies ermöglichte die Durchführung von grundlegenden Experimenten bezüglich Temperatur- und Geschwindigkeitsabhängigkeiten der Reibung von Antimon-Nanopartikeln auf Graphit. Monte-Carlo-Simulationen eines neu entwickelten Nanoskalen-Reibungsmodells erlaubten die Identifikation zweier Prozesse, welche grundlegend zu der Entstehung der beobachteten Reibung beitragen: Kontaktalterung und Thermische Aktivierung. Die Beobachtung von stick-slip-Reibung gestattete schließlich die direkte Quantifizierung der Kontaktalterung. Hierbei wurde eine logarithmische Abhängigkeit der Haftreibung von der Haltezeit festgestellt.Komplementäre Messungen zeigten qualitativ differierendes Verhalten von zwei verschiedenen punktartigen Reibungskontaktsystemen bei unterschiedlichen Temperaturen auf. In Siliziumdioxid-Gold-Kontakten wurde eine Kontaktalterung in Abhängigkeit der Scherbewegung beobachtet, was durch die Formierung einer Gold-Kapillareinschnürung erklärt wird. Kontakte bestehend aus Siliziumdioxid zeigten hingegen Kontaktalterung in stationären Kontakten, vergleichbar zu der Kontaktalterung bei Antimon-Nanopartikeln. Alle Ergebnisse unterstreichen die grundlegende Bedeutung von Kontaktalterung in der nanoskaligen Reibung, im Speziellen für die Reibungskinetik von Nanopartikeln.
Nanopartikelreibung und Kontaktalterung
Keywords: Nanotribologie; Nanopartikel; Kontaktalterung; nanotribology; nanoparticle; contact-ageing; ddc:530